Glass substrate micro energy storage battery and preparation method thereof

By designing micro energy storage batteries on a glass substrate and combining photovoltaic electrodes, the existing micro energy storage batteries have been solved, and efficient energy storage and power supply have been achieved.

CN119764526APending Publication Date: 2025-04-04CENT SOUTH UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411735518.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing micro-energy storage batteries have complex structures, few related research, and have failed to effectively combine photovoltaic electrodes to realize power storage applications after photovoltaic power generation.

Method used

A micro-energy storage battery designed with a glass substrate includes a substrate and a micro-energy storage battery element. The element consists of an anode current collector layer, an anode layer, a solid electrolyte layer, a cathode layer and a cathode current collector layer, and is prepared by vacuum evaporation and spin coating technology.

Benefits of technology

The integration of photovoltaic power generation devices and energy storage devices is realized, the equipment structure is simplified, the energy density and power supply time are improved, and the charge and discharge properties and energy storage performance are excellent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764526A_ABST
    Figure CN119764526A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of micro battery devices, and particularly relates to a glass substrate micro energy storage battery and a preparation method thereof. The glass substrate micro energy storage battery comprises a substrate and a micro energy storage battery element, wherein the substrate is a glass substrate; the miniature energy storage battery element sequentially comprises an anode current collector layer, an anode layer, a solid electrolyte layer, a cathode layer and a cathode current collector layer from bottom to top. According to the glass-substrate micro energy storage battery, the glass is used as the substrate and is matched with interlayer arrangement of the anode current collector layer, the anode layer, the solid electrolyte layer, the cathode layer and the cathode current collector layer, so that the glass-substrate micro energy storage battery has excellent charging and discharging properties and energy storage performance on the premise of no conventional gold foil current collector and other packaging means.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of micro battery devices, and in particular relates to a glass substrate micro energy storage battery and a preparation method thereof. Background Art

[0002] As the main energy source for miniaturized electronic devices in today's society, micro batteries have many advantages, such as small size, light weight, long life, stability and high performance. Despite this, micro batteries still have limited capacity, high cost, and restrictions on how to effectively charge and discharge. With the popularization of portable electronic devices, medical devices and embedded systems, the demand for micro energy storage batteries will continue to grow. Under this premise, the development of micro energy storage batteries can not only meet the current social demand for miniaturized electronic devices, but also promote green energy and sustainable development, bringing more possibilities for future technological development and life.

[0003] At present, there is still a lot of room for improvement in the structural design and preparation process of micro energy storage batteries with special structures, especially in terms of increasing the energy density of micro batteries and increasing their power supply time. Effectively integrating glass-based micro energy storage batteries and photovoltaic electrodes and other devices is one of the directions for sustainable development of green energy. However, the structure of such devices is complex, and there is little research on related existing technologies. At present, there is no optoelectronic device that combines micro energy storage batteries and photovoltaic electrodes, and the practical application of directly charging and storing micro batteries after photovoltaic power generation has not yet been realized.

[0004] Therefore, the development of a new type of glass-based microbattery has broad application prospects and can be effectively combined with small photovoltaic power generation equipment to achieve effective storage of green electricity. Summary of the invention

[0005] The technical problem to be solved by the present invention is that the existing micro energy storage battery has a complex structure and there is little related research. In order to overcome the shortcomings and defects mentioned in the above background technology, a glass-based micro energy storage battery and a preparation method thereof are provided.

[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is: A glass-based micro energy storage battery, comprising a substrate and a micro energy storage battery element, wherein the substrate is a glass substrate; the micro energy storage battery element comprises, from bottom to top, an anode current collector layer, an anode layer, a solid electrolyte layer, a cathode layer and a cathode current collector layer.

[0007] Glass-based microbatteries represent a new type of energy storage technology. Compared with traditional batteries, they have better flexibility and transparency and can adapt to various application scenarios, such as wearable devices, smart buildings, and visualization equipment.

[0008] The overall structure of the glass-based micro energy storage battery is divided from bottom to top into: glass substrate, ITO anode current collector, anode layer, solid electrolyte layer, cathode active material layer, cathode current collector. The current collector mainly plays the role of connecting the external circuit; the anode layer, solid electrolyte layer, and cathode active material layer play the main role of energy storage battery; in addition to embedding the anode, the solid electrolyte layer also blocks the direct contact between the cathode and the anode.

[0009] Preferably, the substrate is a glass substrate of a photovoltaic power generation device, and the size of the glass substrate of the photovoltaic power generation device is 3×3 to 10×10 cm.

[0010] The anode current collector layer includes indium tin oxide; the glass substrate combined with the indium tin oxide anode current collector layer can prepare a transparent energy storage battery, which is suitable for smart windows, solar photovoltaic panels, wearable devices and other fields, and provides energy support for visualization and optical display.

[0011] The present application selects the glass substrate of the photovoltaic power generation device as the glass substrate of the glass substrate micro energy storage battery, and cleverly combines the two devices organically so that the two can appear as the same integral micro device. The glass substrate micro energy storage battery of the present application has the unique advantage of integrating the photovoltaic device and the energy storage device on the glass substrate.

[0012] Conventional photovoltaic integrated equipment connects photovoltaic power generation and energy storage batteries through external lines, while the present application directly prepares a micro energy storage battery on a glass substrate to form an integrated design. The glass substrate can not only generate photovoltaic power, but also store electrical energy through the prepared energy storage device, which can simplify the structure and circuits of the equipment and save space for photovoltaic equipment.

[0013] The power generation efficiency of photovoltaic power generation is generally low, so the design of the corresponding micro energy storage battery on its backplane needs to be combined with the volume and power generation efficiency of the photovoltaic power generation equipment to avoid the problems of reduced power, bloated size, and difficulty in filling the energy storage equipment by itself due to the increase of energy storage batteries. On this basis, this application puts forward higher requirements on the thickness, size, interlayer flatness and stability of the micro energy storage battery.

[0014] 1. Volume and weight optimization: The design of micro energy storage batteries must be strictly controlled in terms of volume and weight to avoid excessive space occupation and increase the weight burden of photovoltaic equipment. This requires the selection of high energy density energy storage materials, such as lithium-ion batteries or other efficient energy storage devices, and ensuring that the battery size matches the photovoltaic substrate.

[0015] 2. Thickness control: The thickness of the micro energy storage battery has a direct impact on the flatness and aesthetics of the entire photovoltaic device. A thinner battery design can not only reduce interference with the overall structure of the photovoltaic panel, but also improve the integration of the device.

[0016] 3. Interlayer flatness and stability: To ensure the interlayer flatness of photovoltaic panels and micro energy storage batteries, the thickness and surface smoothness of each layer of material must be strictly controlled to avoid defects such as unevenness or bubbles, which will not only affect the overall appearance of the equipment, but may also damage the operation of the battery and photovoltaic panels. At the same time, the adhesion and structural stability between layers need to be maintained through specific technologies and preparation processes to ensure the reliable operation of energy storage equipment.

[0017] The substrate is a glass substrate of a photovoltaic power generation device; More preferably, the size of the glass substrate of the photovoltaic power generation device is 3×3 to 10×10 cm The anode current collector layer includes indium tin oxide; The anode layer includes high purity alkali metal and / or copper; More preferably, the anode layer comprises metallic lithium and / or metallic copper; more preferably metallic lithium.

[0018] The solid electrolyte layer includes an electrolyte filler, a binder and a lithium salt; The binder is polyethylene oxide and / or polyvinylidene fluoride, more preferably polyethylene oxide; The electrolyte filler comprises one or more of fumed silica, alumina or zirconia, more preferably fumed silica; The lithium salt includes one or more of lithium nitrate, lithium hexafluorophosphate or lithium bis(trifluoromethanesulfonyl)imide, more preferably lithium bis(trifluoromethanesulfonyl)imide; The cathode layer comprises a cathode active material, a binder and conductive carbon black, wherein the binder is polyethylene oxide and / or polyvinylidene fluoride, and the cathode active material comprises one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganate or sulfur, more preferably lithium iron phosphate or sulfur; The cathode current collector layer comprises silver and / or aluminum, more preferably aluminum.

[0019] Preferably, the anode layer is evaporated on the anode current collector layer, the thickness of the anode layer is 100~500 nm, and the area of ​​the anode covering the anode current collector layer does not exceed 90% of the area of ​​the glass substrate; the high-purity alkali metal includes one or more of metallic sodium, metallic potassium or metallic lithium with a purity exceeding 99.99%.

[0020] Preferably, the thickness of the solid electrolyte layer is 500-1500 nm, the mass of the electrolyte filler is about 10-30% of the total mass of the binder and the lithium salt, and the binder and the lithium salt are Li + The molar ratio is 2:1~30:1 More preferably, the electrolyte filler in the solid electrolyte layer is SiO2, the binder is PEO, and the lithium salt is LiTFSI, and the mass ratios thereof are PEO:LiTFSI:SiO2=0.44:0.1435:0.0875 respectively.

[0021] Preferably, the cathode active material in the cathode layer is lithium iron phosphate, the binder is PVDF, the mass ratio of lithium iron phosphate, conductive carbon black and PVDF is 2.5-18:1-3:1, and the thickness of the cathode layer is 1000~3000 nm; the cathode current collector layer is evaporated on the cathode layer, and the thickness of the cathode current collector layer is 50~100 nm.

[0022] Under the same technical concept, the present invention also provides a method for preparing the glass substrate micro energy storage battery, comprising the following steps: (1) Evaporating the anode current collector layer on the substrate, cleaning and drying; (2) evaporating an anode layer on the anode current collector layer; (3) preparing a mixed solution of raw materials for a solid electrolyte layer, and spin-coating the mixed solution of raw materials for the solid electrolyte layer on the anode layer to obtain a solid electrolyte layer; (4) preparing a raw material slurry for a cathode layer, and spin-coating the raw material slurry for the cathode layer on the solid electrolyte layer to obtain a cathode layer; (5) Evaporating a cathode current collector layer on the cathode layer, cutting and arranging the cathode layer, and obtaining a glass-based micro energy storage battery.

[0023] Through the limitation of the mask, after evaporating an anode layer of a certain thickness in a specific area, the viscous liquid electrolyte is attached to the top of the metallic lithium through spin coating and then heated and dried, so that the obtained solid electrolyte can cover the anode layer well and completely isolate it from the external environment.

[0024] Preferably, the cleaning in step (1) is performed by ultrasonic cleaning, and the solvent for the ultrasonic cleaning includes isopropyl ketone and / or isopropyl alcohol; the drying process is performed in a vacuum drying oven; and the evaporation in steps (1) and (2) is performed under the vacuum conditions of a vacuum evaporation equipment.

[0025] More preferably, the vacuum evaporation equipment is provided with a thickness monitoring system and a spin coating system, and a mask of a corresponding customized shape is used during evaporation.

[0026] In this application, the thickness of the anode layer is in the nanometer or micrometer level, and the preparation process needs to be operated under the high vacuum conditions of the vacuum evaporation equipment. The interference of gas molecules can be effectively reduced in the equipment, so that the evaporated material can propagate in a straight line in a vacuum. This environment ensures that the material is uniformly deposited on the substrate, reduces the scattering phenomenon caused by gas collisions, and thus improves the uniformity of the film layer. A heating source or an electron beam source is usually used in the evaporation equipment to evaporate the material, and the evaporation rate of the material can be accurately controlled. By adjusting the temperature or energy of the evaporation source, the evaporation rate of the material can be accurately controlled, thereby achieving accurate control of the deposition thickness.

[0027] In actual operation, the substrate is usually in a rotating state to ensure that the evaporated material is evenly deposited in various areas of the substrate. The design of the rotating substrate allows the material to reach the substrate surface evenly from different angles, effectively preventing the problem of local uneven deposition. Vacuum evaporation equipment is usually equipped with a crystal oscillator monitor or other thickness monitoring system, which can monitor the growth rate and thickness of the film layer in real time. This real-time monitoring allows the operator to accurately adjust the evaporation rate during the deposition process to achieve the target thickness. By controlling parameters such as vacuum degree, evaporation rate, substrate temperature, and evaporation time, the operator can accurately control the thickness of the evaporated layer. In addition, the adjustment of gas flow and pressure can also affect the deposition rate of the material, making thickness control more flexible.

[0028] Preferably, the step (3) of preparing the raw material mixed solution of the solid electrolyte layer specifically comprises: mixing the electrolyte filler, the binder and the lithium salt according to a mass ratio, dissolving them in a solvent, and stirring them at a speed of 350-450 rpm and 48-55° C. for 4.5-5.5 h to obtain the raw material mixed solution of the solid electrolyte layer; the spin coating rate is 1000-6000 rpm.

[0029] More preferably, the solid electrolyte is configured in a glove box filled with inert gas Ar gas, and the environmental requirements of the glove box are: water content is less than 0.1 ppm; oxygen content is less than 0.1 ppm; Preferably, the preparation of the raw material slurry for the cathode layer in step (4) specifically includes: mixing the cathode active material, the binder and the conductive carbon black according to a mass ratio, dissolving them in a solvent, and stirring them at a speed of 250-350 rpm for 4.5-5.5h to obtain the raw material slurry for the cathode layer; the spin coating speed is 1000-6000 rpm.

[0030] More preferably, the raw material slurry is prepared in a glove box filled with inert Ar gas, and the environmental requirements of the glove box are: water content less than 0.1ppm; oxygen content less than 0.1ppm; airtightness: leakage rate ≤0.05Vol% / h, so as to prevent water and oxygen from affecting the inside of the battery.

[0031] More preferably, the cutting in step (5) is performed by machine using a scraper.

[0032] Compared with the prior art, the present invention has the following beneficial effects: (1) The glass-based micro energy storage battery of the present invention uses glass as a substrate, and has an interlayer design of an anode current collector layer, an anode layer, a solid electrolyte layer, a cathode layer, and a cathode current collector layer. Without conventional gold foil current collectors or other packaging methods, it has excellent charge and discharge properties and energy storage performance; (2) Energy storage batteries prepared using glass substrates can be used for automated battery testing, enabling daily energy management and providing effective testing for studying energy efficiency and system stability; (3) The glass-based micro energy storage battery of the present application can be combined with other devices using a glass substrate, such as photovoltaic power generation devices, to achieve the integration of optoelectronic devices, providing basic support for the design of new miniaturized electronic devices; (4) The preparation method of the present invention is simple to operate and has industrial feasibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 This is a schematic cross-sectional view of the glass-based micro energy storage battery prepared in Example 1; Figure 2 Schematic top view of the glass substrate micro energy storage battery prepared in Example 1; Figure 3 This is a diagram of the metal lithium evaporated on the ITO glass encapsulated by the solid electrolyte in Example 1; Figure 4 This is a diagram of a glass substrate micro energy storage battery device prepared in Example 1; Figure 5 Graph showing the diffusion of lithium ions in the PEO solid electrolyte in Example 1 and Example 2; Figure 6 This is a charge and discharge voltage platform diagram of the glass-based micro energy storage battery prepared in Example 1; Figure 7 This is a charge and discharge cycle diagram of the glass-based micro energy storage battery prepared in Example 1; Figure 8 This is a schematic cross-sectional view of the glass-based micro energy storage battery prepared in Example 2; Fig. 9 A schematic top view of a glass-based micro energy storage battery prepared in Example 2; Fig.10 This is a charge and discharge voltage platform diagram of the glass-based micro energy storage battery prepared in Example 2; Fig.11 This is a charge and discharge cycle diagram of the glass-based micro energy storage battery prepared in Example 2; Fig.12 This is a charge and discharge voltage platform diagram of the glass-based micro energy storage battery prepared in Comparative Example 1; Fig.13 This is a charge and discharge cycle diagram of the glass-based micro energy storage battery prepared in Comparative Example 1; Fig.14 This is an integrated conceptual diagram of a glass-based micro energy storage battery. DETAILED DESCRIPTION

[0035] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0036] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0037] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0038] The present application embodiment selects the chemical materials required for preparation and controls the quality, purity, concentration, fineness and precision. The specific selection is as follows: Deionized water: Liquid; Isopropyl alcohol: liquid, purity: analytical grade; Conductive glass (indium tin oxide ITO): solid, transmittance about 92%, square resistance 15 Ω cm; Lithium: solid cylindrical particles, volume φ3 mm*3 mm, purity 99.99%; PEO: solid powder, molecular weight ~600,000; Conductive carbon black: solid powder, purity 99%; Lithium iron phosphate: solid powder, particle size 1~3 um, purity 99.5%; Lithium bis(trifluoromethanesulfonyl)imide: solid powder, purity 99.5%.

[0039] Embodiment 1: This embodiment provides a glass substrate micro energy storage battery, the battery structure includes a substrate and a micro energy storage battery element, the substrate is a glass substrate of a photovoltaic power generation device; the micro energy storage battery element is composed of an anode current collector layer, an anode layer, a solid electrolyte layer, a cathode layer and a cathode current collector layer; Photovoltaic devices are prepared on glass substrates in advance, and the overall structure is as follows Fig.14 As shown: First, glass is used as a substrate, and a transparent conductive oxide (TCO) film is coated on the glass substrate as a transparent front electrode; a light absorbing material is deposited on the TCO layer; a buffer layer is deposited on the absorbing layer; a metal back electrode is deposited on the buffer layer; finally, the prepared photovoltaic device is packaged and assembled with EVA or PVB and an ultra-white embossed glass cover to protect the device and improve its stability and durability; The size of the glass substrate used was 3 × 3 cm; The anode current collector layer is ITO, which is attached to the glass substrate as a base layer and has a thickness of 150 nm; The anode layer is located above the anode current collector layer. The anode layer is metallic lithium with a purity of more than 99.99% and a thickness of 500 nm. The area of ​​the anode covering the anode current collector layer does not exceed 90% of the area of ​​the glass substrate. Above the anode layer is a solid electrolyte layer with a thickness of 1500 nm; the solid electrolyte layer includes PEO, LiTFSI and SiO2, with the amount of PEO added being 0.44 g, the amount of LiTFSI added being 0.1435 g, and the amount of SiO2 added being 0.0875 g; The cathode layer is located above the solid electrolyte layer. The active materials are lithium iron phosphate, conductive carbon black and PVDF. The mass ratio is 8:1:1. The added amounts are 1280 mg, 160 mg and 160 mg respectively. The thickness is 3000 nm. Above the cathode layer is the cathode current collector layer with a thickness of 100 nm.

[0040] The battery structure of glass-based micro energy storage battery is as follows Figure 1-4 As shown; Figure 1 This is a schematic cross-sectional view of the glass-based micro energy storage battery prepared in Example 1; Figure 2 Schematic top view of the glass substrate micro energy storage battery prepared in Example 1; Figure 3 This is a diagram of the metal lithium evaporated on the ITO glass encapsulated by the solid electrolyte in Example 1; Figure 4 This is a picture of the glass-based micro energy storage battery device prepared in Example 1.

[0041] This embodiment provides a method for preparing a glass substrate micro energy storage battery, and the specific steps are as follows: The equipment used in the preparation includes: vacuum evaporation apparatus, spin coater, temperature-controlled heating table, etc.; 1. Preparation and treatment of anode current collector layer Take 10 glass substrates prepared with photovoltaic devices, use a vacuum evaporator to evaporate the ITO anode current collector layer on the substrate to obtain an ITO conductive glass sheet; use a cotton swab dipped in an appropriate amount of detergent to wipe the glass sheet and rinse it with clean water, ultrasonically clean it with deionized water for 15 minutes, then ultrasonically clean it with isopropyl alcohol for 15 minutes, and then dry it in a vacuum drying oven; place the dried ITO conductive glass sheet in a UV ozone cleaner for 30 minutes for use.

[0042] 2. Preparation and treatment of anode layer (1) The ITO conductive glass sheet is transferred to a vacuum deposition chamber, and the substrate is fixed on a turntable at the top of the customized deposition chamber, with the substrate coated with the anode current collector layer facing downward; (2) Placing lithium particles in a tungsten boat in a vapor deposition container; (3) Adjust the quartz thickness probe and quartz monitoring probe on the furnace wall so that the quartz thickness probe is aligned with the substrate on the turntable and the quartz monitoring probe is aligned with the placed lithium particles; (4) Close the door of the vacuum deposition chamber and seal it; (5) Turn on the mechanical vacuum pump and molecular vacuum pump to make the vacuum degree in the evaporation chamber ≤ 1.5×10 -4 Pa, and keep it constant; (6) The instrument evaporation rate is set to 3 Å / s, i.e. 0.3 nm / s, and the corresponding current is set to adjust the evaporation rate until a stable rate is achieved; (6) Turn on the turntable, and the conductive glass will rotate accordingly. Turn on the turntable, and the conductive glass will rotate accordingly; (7) Evaporation of lithium metal anode current collector: Turn on the tungsten boat power supply to evaporate lithium particles from solid to gaseous state, and the gaseous molecules are deposited and grown on the interface layer. Adjust the power to maintain the film growth rate at 0.1 Å / s and the film thickness at 300 nm. During the preparation process, the quartz thickness probe measures the evaporation thickness, and the thickness value is displayed on the display screen. Pay attention to the evaporation condition during the process. (8) After the anode current collector layer is evaporated, the prepared anode current collector layer micro energy storage battery is left to cool for 10 min under vacuum for use.

[0043] 3. Preparation and treatment of solid electrolyte layer (1) Weigh PEO, lithium bis(trifluoromethanesulfonyl)imide and fumed nano-silica separately and place them in a 20 mL transparent reagent bottle with a magnetic stirrer; (2) Measure 10 μL of acetonitrile solvent and add it into the above transparent reagent bottle; (3) The reagent bottle was placed on a magnetic stirrer and stirred at 300 rpm for 5 h under heating conditions of 55°C to obtain a raw material mixed solution of a solid electrolyte layer prepared by mixing PEO, lithium bis(trifluoromethanesulfonyl)imide and nano-silicon dioxide in a certain mass ratio; in this embodiment, the amount of PEO added was 0.44 g, the amount of LiTFSI added was 0.1435 g, and the amount of SiO2 added was 0.0875 g. The solid electrolyte solution was subjected to ultrasonic defoaming treatment before use.

[0044] (4) Place the ITO conductive glass sheet with the lithium layer evaporated on a coating machine for adsorption. Set the speed of the coating machine to 2500 rpm. Then, take the prepared solution with a pipette and spin coat it on the anode layer to cover the anode layer. Place the glass sheet coated with a uniform solid electrolyte layer on a heating table for thermal annealing at 60°C for 10 minutes for use.

[0045] 4. Preparation and treatment of cathode layer (1) Weigh lithium iron phosphate, conductive carbon black, and PEO (1280 mg: 160 mg: 160 mg) respectively and place them in a 20 mL transparent reagent bottle with a magnetic stirrer; (2) Measure 6000 μL of NMP solvent and add it into the above transparent reagent bottle; (3) The solution was placed on a magnetic stirrer and stirred at 300 rpm for 5 h at room temperature to fully mix the materials and obtain a raw material slurry for the cathode layer with a mass ratio of lithium iron phosphate, conductive carbon black and PVDF of 8:1:1; (4) Continue to place the ITO conductive glass sheet coated with the solid electrolyte layer on the coating machine, set the speed to 2000 rpm, then use a pipette to transfer the prepared cathode solution and drop it on the solid electrolyte layer; and place the glass sheet coated with a uniform cathode layer on a heating table for thermal annealing at 70°C for 20 minutes for use.

[0046] (5) Scrape off part of the preparation layer to expose part of the ITO layer, forming a battery structure in which the positive and negative electrodes of the battery do not contact each other.

[0047] 5. Preparation and treatment of cathode current collector layer (1) The ITO conductive glass sheet with the cathode layer spin-coated is transferred to a vacuum evaporation chamber, and the substrate is fixed on a turntable at the top of the evaporation chamber, with the cathode layer spin-coated substrate facing downward; (2) placing aluminum particles in a tungsten boat in a vapor deposition container; (3) Adjust the quartz thickness probe and quartz monitoring probe on the furnace wall so that the quartz thickness probe is aligned with the substrate on the turntable and the quartz monitoring probe is aligned with the placed aluminum particles; (4) Close the door of the vacuum deposition chamber and seal it; (5) Turn on the mechanical vacuum pump and molecular vacuum pump to make the vacuum degree in the evaporation chamber ≤ 1.5×10 -4 Pa, and keep it constant; (6) The instrument evaporation rate is set to 3 Å / s, i.e. 0.3 nm / s, and the corresponding current is set to adjust the evaporation rate until a stable rate is achieved; (6) Turn on the turntable, and the conductive glass will rotate accordingly. Turn on the turntable, and the conductive glass will rotate accordingly; (7) Evaporation of aluminum metal current collector: Turn on the tungsten boat power supply to evaporate aluminum particles from solid to gas, and the gas molecules are deposited and grown on the interface layer. Adjust the power to maintain the film growth rate at 0.1 Å / s and the film thickness at about 100 nm. During the preparation process, the quartz thickness probe measures the evaporation thickness, and the thickness value is displayed on the display screen. Pay attention to the evaporation condition during the process. (8) After the cathode current collector layer is evaporated, the pressure in the evaporation chamber is adjusted to normal pressure by inflating the chamber, and then the chamber is opened to take out the device, and part of the preparation layer is scraped off to expose part of the ITO layer, forming a battery structure in which the positive and negative electrodes of the battery do not contact each other, thereby obtaining a glass-based micro energy storage battery.

[0048] The glass substrate micro energy storage battery is assembled. The assembly environment requirements of the device are: water content less than 0.1 ppm; oxygen content less than 0.1 ppm. Airtightness: leakage rate ≤ 0.05Vol% / h to prevent water and oxygen from affecting the inside of the battery. After assembly, the electrochemical performance test is carried out according to the method mentioned in the national standard GB / T 36276-2018.

[0049] Figure 5 Graph showing the diffusion of lithium ions in the PEO solid electrolyte in Example 1 and Example 2; The prepared glass-based microbattery was tested for impedance at frequencies ranging from 10,000 Hz to 0.01 Hz using the AC impedance test method, and the lithium ion mobility in the device was calculated based on the effect data.

[0050] Figure 6 This is a charge and discharge voltage platform diagram of the glass-based micro energy storage battery prepared in Example 1; The charge and discharge voltage platform diagram obtained by charging and discharging the glass-based micro battery in the potential range of 2.5 - 3.7 V. The test results prove that the glass-based micro energy storage battery prepared with lithium iron phosphate as the positive electrode, metallic lithium as the negative electrode, and PEO-LiEFSI-SiO2 as the solid electrolyte can be normally charged and discharged.

[0051] Figure 7This is a charge and discharge cycle diagram of the glass-based micro energy storage battery prepared in Example 1; The charge and discharge cycle test diagram of a glass-based micro energy storage battery prepared with lithium iron phosphate as the positive electrode, metallic lithium as the negative electrode, and PEO-LiEFSI-SiO2 as the solid electrolyte. The battery is small in size, but has a certain charge and discharge capacity and can be charged and discharged smoothly, and has a high coulombic efficiency.

[0052] Embodiment 2: This embodiment provides a glass substrate micro energy storage battery with a glass substrate, wherein the battery structure includes a substrate and a micro energy storage battery element, and the micro energy storage battery element is composed of an anode current collector layer, an anode layer, a solid electrolyte layer, a cathode layer and a cathode current collector layer; The anode current collector layer is ITO, which is attached to the glass substrate as a base layer and has a thickness of 150 nm; Above the anode current collector layer is the anode layer, which is made of metallic lithium with a purity of more than 99.99% and a thickness of 500 nm; Above the anode layer is a solid electrolyte layer with a thickness of 1500 nm; the solid electrolyte layer includes 440 mg of PEO, 143.5 mg of lithium bis(trifluoromethanesulfonyl)imide and 87.5 mg of gas-phase nano-silica; The cathode layer is located above the solid electrolyte layer. The active materials are sulfur / carbon nanotube composite material, conductive carbon black and PVDF, with a mass of 960 mg:160 mg:320 mg respectively and a thickness of 3000 nm. Above the cathode layer is the cathode current collector layer with a thickness of 100 nm.

[0053] Figure 8 This is a schematic cross-sectional view of the glass-based micro energy storage battery prepared in Example 2; Fig. 9 A schematic top view of a glass-based micro energy storage battery prepared in Example 2; The preparation method of the glass substrate micro energy storage battery provided in this embodiment is as follows: The equipment used in the preparation includes: vacuum evaporation apparatus, spin coater, temperature-controlled heating table, etc.; 1. Preparation and treatment of anode current collector layer Take 10 glass substrates, use a vacuum evaporator to evaporate the ITO anode current collector layer on the substrate to obtain an ITO conductive glass sheet; use a cotton swab dipped in an appropriate amount of detergent to wipe the glass sheet and rinse it with clean water, then use deionized water for ultrasonic cleaning for 15 minutes; then use isopropyl alcohol for ultrasonic cleaning for 15 minutes, and then dry it in a vacuum drying oven; place the dried ITO conductive glass sheet in a UV ozone cleaning machine for 30 minutes for use.

[0054] 2. Preparation and treatment of anode layer (1) The ITO conductive glass sheet is transferred to a vacuum deposition chamber, and the substrate is fixed on a turntable at the top of the customized deposition chamber, with the substrate coated with the anode current collector layer facing downward; (2) Placing lithium particles in a tungsten boat in a vapor deposition container; (3) Adjust the quartz thickness probe and quartz monitoring probe on the furnace wall so that the quartz thickness probe is aligned with the substrate on the turntable and the quartz monitoring probe is aligned with the placed lithium particles; (4) Close the door of the vacuum deposition chamber and seal it; (5) Turn on the mechanical vacuum pump and molecular vacuum pump to make the vacuum degree in the evaporation chamber ≤ 1.5×10 -4 Pa, and keep it constant; (6) The instrument evaporation rate is set to 3 Å / s, i.e. 0.3 nm / s, and the corresponding current is set to adjust the evaporation rate until a stable rate is achieved; (6) Turn on the turntable, and the conductive glass will rotate accordingly. Turn on the turntable, and the conductive glass will rotate accordingly; (7) Evaporation of lithium metal anode current collector: Turn on the tungsten boat power supply to evaporate lithium particles from solid to gaseous state, and the gaseous molecules are deposited and grown on the interface layer. Adjust the power to maintain the film growth rate at 0.1 Å / s and the film thickness at about 300 nm. During the preparation process, the quartz thickness probe measures the evaporation thickness, and the thickness value is displayed on the display screen. Pay attention to the evaporation condition during the process. (8) After the anode current collector layer is evaporated, the prepared anode current collector layer micro energy storage battery is left to cool for 10 min under vacuum for use.

[0055] 3. Preparation and treatment of solid electrolyte layer (1) Weigh 440 mg of PEO, 143.5 mg of lithium bis(trifluoromethanesulfonyl)imide, and 87.5 mg of fumed nano-silica into a 20 mL transparent reagent bottle with a magnetic stirrer; (2) Measure 10 μL of acetonitrile solvent and add it into the above transparent reagent bottle; (3) The reagent bottle was placed on a magnetic stirrer and stirred at 300 rpm for 5 h under heating conditions of 55° C. to obtain a solid electrolyte layer solution containing PEO, lithium bis(trifluoromethanesulfonyl)imide and gas-phase nano-silica; the solid electrolyte solution was subjected to ultrasonic defoaming treatment before use.

[0056] (4) Place the ITO conductive glass sheet with the lithium layer evaporated on a coating machine for adsorption. Set the speed of the coating machine to 2500 rpm. Then, take the prepared solution with a pipette and spin coat it on the anode layer to cover the anode layer. Place the glass sheet coated with a uniform solid electrolyte layer on a heating table for thermal annealing at 60°C for 10 minutes for use.

[0057] 4. Preparation and treatment of cathode layer (1) Elemental sulfur and carbon nanotubes were ball-milled in a mass ratio of 4:1, and heated to react at 160° C. for 12 hours in a protective argon atmosphere to obtain a sulfur / carbon nanotube composite material.

[0058] (2) Place sulfur / carbon nanotube composite material, conductive carbon black and PVDF (960 mg:160 mg:320 mg) in a 20 mL transparent reagent bottle with a magnetic stirrer; (2) Measure 4000 μL of NMP solvent and add it into the above transparent reagent bottle; (3) placing the solution on a magnetic stirrer and stirring at 300 rpm at room temperature to fully mix the materials, thereby obtaining a cathode slurry having a sulfur / carbon nanotube composite material and a conductive carbon black and PVDF mass ratio of 6:1:2; (4) Continue to place the ITO conductive glass sheet coated with the solid electrolyte layer on a coating machine, set the speed to 2000 rpm, then use a pipette to transfer the prepared cathode solution, and drop it on the solid electrolyte layer by spin coating; and place the glass sheet coated with a uniform cathode layer on a heating table for thermal annealing at 80°C for 20 minutes for use.

[0059] (5) Scrape off part of the preparation layer to expose part of the ITO layer, forming a battery structure in which the positive and negative electrodes of the battery do not contact each other.

[0060] 5. Preparation and treatment of cathode current collector layer (1) The ITO conductive glass sheet with the cathode layer spin-coated is transferred to a vacuum evaporation chamber, and the substrate is fixed on a turntable at the top of the evaporation chamber, with the cathode layer spin-coated substrate facing downward; (2) placing aluminum particles in a tungsten boat in a vapor deposition container; (3) Adjust the quartz thickness probe and quartz monitoring probe on the furnace wall so that the quartz thickness probe is aligned with the substrate on the turntable and the quartz monitoring probe is aligned with the placed aluminum particles; (4) Close the door of the vacuum deposition chamber and seal it; (5) Turn on the mechanical vacuum pump and molecular vacuum pump to make the vacuum degree in the evaporation chamber ≤ 1.5×10 -4 Pa, and keep it constant; (6) The instrument evaporation rate is set to 3 Å / s, i.e. 0.3 nm / s, and the corresponding current is set to adjust the evaporation rate until a stable rate is achieved; (6) Turn on the turntable, and the conductive glass will rotate accordingly. Turn on the turntable, and the conductive glass will rotate accordingly; (7) Evaporation of aluminum metal current collector: Turn on the tungsten boat power supply to evaporate aluminum particles from solid to gas, and the gas molecules are deposited and grown on the interface layer. Adjust the power to maintain the film growth rate at 0.1 Å / s and the film thickness at about 100 nm. During the preparation process, the quartz thickness probe measures the evaporation thickness, and the thickness value is displayed on the display screen. Pay attention to the evaporation condition during the process. (8) After the cathode current collector layer is evaporated, the pressure in the evaporation chamber is adjusted to normal pressure by inflating the chamber, and then the chamber is opened to take out the device, and part of the preparation layer is scraped off to expose part of the ITO layer, forming a battery structure in which the positive and negative electrodes of the battery do not contact each other, thereby obtaining a glass-based micro energy storage battery.

[0061] The glass substrate micro energy storage battery is assembled. The assembly environment requirements of the device are: water content less than 0.1 ppm; oxygen content less than 0.1 ppm. Airtightness: leakage rate ≤ 0.05Vol% / h to prevent water and oxygen from affecting the inside of the battery. After assembly, the electrochemical performance test is carried out according to the method mentioned in the national standard GB / T 36276-2018.

[0062] Fig.10 This is a charge and discharge voltage platform diagram of the glass-based micro energy storage battery prepared in Example 2; The charge and discharge voltage platform diagram obtained by charging and discharging the glass-based micro battery in the potential range of 1.0 - 3.0 V. The test results prove that the glass-based micro energy storage battery prepared with sulfur as the positive electrode, metallic lithium as the negative electrode, and PEO-LiEFSI-SiO2 as the solid electrolyte can be normally charged and discharged.

[0063] Fig.11 This is the charge and discharge cycle diagram of the glass-based micro energy storage battery prepared in Example 2.

[0064] The charge and discharge cycle test diagram of a glass-based micro energy storage battery prepared with sulfur as the positive electrode, metallic lithium as the negative electrode, and PEO-LiEFSI-SiO2 as the solid electrolyte. Theoretically, this battery size has a higher charge and discharge capacity.

[0065] Example 2 demonstrates that a variety of different types of glass-based micro energy storage batteries can be prepared using this method.

[0066] Comparative Example 1: This comparative example provides a method for preparing a glass-based micro energy storage battery by scraping, wherein the battery structure consists of an anode current collector layer, an anode layer, a solid electrolyte layer, a cathode layer and a cathode current collector layer.

[0067] The following are the detailed scraper preparation steps: 1. Preparation and treatment of anode current collector layer (1) Take 10 glass substrates coated with ITO layers, wipe the glass sheets with a cotton swab dipped in an appropriate amount of detergent and rinse them with clean water, then ultrasonically clean them with deionized water for 15 minutes, then ultrasonically clean them with isopropyl alcohol for 15 minutes, and then dry them in a vacuum drying oven; (2) Place the dried ITO conductive glass sheet in a UV ozone cleaning machine for 30 minutes for later use.

[0068] 2. Preparation and treatment of the anode layer (1) Place the ITO conductive glass sheet in the slot of the scraper and fix it in front of the scraper, with the base surface with the anode current collector layer facing upwards; (2) placing lithium particles in a heating container and heating them to melt; (3) Place a certain amount of liquid lithium on one side of the ITO conductive glass sheet, and use a scraper with adjustable thickness to quickly scrape the liquid metal lithium so that the thickness of the anode metal lithium layer is about 500 um; (4) The prepared anode layer is cooled under vacuum to solidify the metal liquid; (5) After the metallic lithium solidifies, scrape off the excess lithium and set aside.

[0069] 3. Preparation and treatment of solid electrolyte layer (1) Weigh 440 mg of PEO, 143.5 mg of lithium bis(trifluoromethanesulfonyl)imide, and 87.5 mg of fumed nano-silica into a 20 mL transparent reagent bottle with a magnetic stirrer; (2) adding 10 μL of acetonitrile solvent, placing on a magnetic stirrer, stirring at a rate of 300 rpm for 5 hours at 55°C to obtain a solid electrolyte layer solution, and performing ultrasonic degassing before use; (3) The ITO conductive glass sheet covered with a lithium metal layer is placed in the slot of the scraper and fixed to the front section of the scraper, with the base surface with the anode current collector layer facing upwards; (4) taking a certain amount of solid electrolyte layer solution and placing it on one side of the ITO conductive glass sheet, and using a scraper with adjustable thickness to quickly scrape the liquid solid electrolyte layer solution to prepare a solid electrolyte layer with a certain thickness; (5) The prepared solid electrolyte layer is left to cool and solidify under vacuum conditions for later use.

[0070] 4. Preparation and treatment of cathode layer (1) Place lithium iron phosphate, conductive carbon black and PEO (1280 mg:160 mg:160 mg) in a 20 mL transparent reagent bottle with a magnetic stirrer; (2) Measure 6000 μL of NMP solvent and add it into the above transparent reagent bottle; (3) The solution was placed on a magnetic stirrer and stirred at 300 rpm at room temperature to fully mix the materials, thereby obtaining a cathode slurry having a mass ratio of lithium iron phosphate, conductive carbon black and PVDF of 8:1:1; (4) The ITO conductive glass sheet covered with a solid electrolyte layer is placed in the slot of the coating equipment and fixed to the front section of the scraper, with the base surface with the solid electrolyte layer facing upwards; (5) Take a certain amount of cathode slurry and place it on one side of the ITO conductive glass sheet. Use a scraper with adjustable thickness to quickly scrape the cathode slurry to prepare a cathode layer with a certain thickness.

[0071] 5. Preparation and treatment of cathode current collector layer (1) Fix the ITO conductive glass sheet with the cathode layer coated on the spin coating chuck, with the substrate with the cathode layer coated facing upwards; (2) preparing a carbon-coated aluminum foil of a specific size and shape with a thickness of 150 μm as the cathode current collector layer; (3) Coating a certain amount of conductive glue on the surface of the cathode layer; (4) The cathode current collector carbon-coated aluminum foil is firmly attached to the surface of the cathode layer and pressed to make it fit tightly with the cathode layer; The glass substrate micro energy storage battery is assembled. The assembly environment requirements of the device are: water content less than 0.1 ppm; oxygen content less than 0.1 ppm. Airtightness: leakage rate ≤ 0.05Vol% / h to prevent water and oxygen from affecting the inside of the battery. After assembly, the electrochemical performance test is carried out according to the method mentioned in the national standard GB / T 36276-2018.

[0072] Comparative Example 1 uses the traditional scraping method, and the thickness is increased, but there is a big difference in roughness and precision; the methods mentioned in Examples 1 and 2 can more conveniently prepare various types of glass-based micro energy storage batteries. The preparation control of different functional layers can be more precise, the operation automation is higher, and the consistency of the prepared devices is higher.

Claims

1. A glass-based micro energy storage battery, characterized in that: The glass substrate micro energy storage battery comprises a substrate and a micro energy storage battery element, wherein the substrate is a glass substrate; The micro energy storage battery element comprises, from bottom to top, an anode current collector layer, an anode layer, a solid electrolyte layer, a cathode layer and a cathode current collector layer.

2. The glass-based micro energy storage battery according to claim 1, characterized in that: The substrate is a glass substrate of a photovoltaic power generation device; The anode current collector layer includes indium tin oxide; The anode layer includes high purity alkali metal and / or copper; The solid electrolyte layer comprises an electrolyte filler, a binder and a lithium salt, wherein the binder is polyethylene oxide and / or polyvinylidene fluoride, the electrolyte filler comprises one or more of fumed silica, alumina or zirconium oxide, and the lithium salt comprises one or more of lithium nitrate, lithium hexafluorophosphate or lithium bis(trifluoromethanesulfonyl)imide; The cathode layer comprises a cathode active material, a binder and conductive carbon black, wherein the binder is polyethylene oxide and / or polyvinylidene fluoride, and the cathode active material comprises one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide or sulfur; The cathode current collector layer includes silver and / or aluminum.

3. The glass-based micro energy storage battery according to claim 2, characterized in that: The anode layer is evaporated on the anode current collector layer, the thickness of the anode layer is 100-500 nm, and the area of ​​the anode covering the anode current collector layer does not exceed 90% of the area of ​​the glass substrate; The high-purity alkali metal includes one or more of metallic sodium, metallic potassium or metallic lithium with a purity exceeding 99.99%.

4. The glass-based micro energy storage battery according to claim 2, characterized in that: The thickness of the solid electrolyte layer is 500-1500 nm, the mass of the electrolyte filler is 10-30% of the total mass of the binder and the lithium salt, and the binder and the lithium salt are Li + The molar ratio is (2:1)~(30:1).

5. The glass-based micro energy storage battery according to claim 4, characterized in that: The electrolyte filler in the solid electrolyte layer is SiO2, the binder is PEO, and the lithium salt is LiTFSI, and the mass ratio thereof is PEO:LiTFSI:SiO2=0.44:0.1435:0.0875.

6. The glass-based micro energy storage battery according to claim 2, characterized in that: The cathode active material in the cathode layer is lithium iron phosphate, the binder is PVDF, the mass ratio of lithium iron phosphate, conductive carbon black and PVDF is 2.5-18:1-3:1, and the thickness of the cathode layer is 1000-3000 nm; the cathode current collector layer is evaporated on the cathode layer, and the thickness of the cathode current collector layer is 50-100 nm.

7. A method for preparing a glass-based micro energy storage battery according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Evaporating the anode current collector layer on the substrate, cleaning and drying; (2) evaporating an anode layer on the anode current collector layer; (3) preparing a mixed solution of raw materials for a solid electrolyte layer, and spin-coating the mixed solution of raw materials for the solid electrolyte layer on the anode layer to form a solid electrolyte layer; (4) preparing a raw material slurry for a cathode layer, and spin coating the raw material slurry for the cathode layer on the solid electrolyte layer to form a cathode layer; (5) Evaporating a cathode current collector layer on the cathode layer, cutting and arranging the cathode layer, and obtaining a glass-based micro energy storage battery.

8. The preparation method according to claim 7, characterized in that: The cleaning in step (1) is performed by ultrasonic cleaning, and the solvent for the ultrasonic cleaning includes isopropyl ketone and / or isopropyl alcohol; the drying is performed in a vacuum drying oven; and the evaporation in steps (1) and (2) is performed under the vacuum conditions of a vacuum evaporation device.

9. The preparation method according to claim 7, characterized in that: The step (3) of preparing the raw material mixed solution of the solid electrolyte layer specifically comprises: mixing the electrolyte filler, the binder and the lithium salt according to a mass ratio, dissolving them in a solvent, and stirring them at a speed of 350-450 rpm and 48-55° C. for 4.5-5.5 h to obtain the raw material mixed solution of the solid electrolyte layer; the spin coating rate is 1000-6000 rpm.

10. The preparation method according to claim 7, characterized in that: The step (4) of preparing the raw material slurry for the cathode layer specifically comprises: mixing the cathode active material, the binder and the conductive carbon black, dissolving them in a solvent, and stirring them at a speed of 250-350 rpm for 4.5-5.5h to obtain the raw material slurry for the cathode layer; the spin coating speed is 1000-6000 rpm.

Citation Information

Patent Citations

  • A high-cycle-life all-solid-state thin-film lithium battery and its fabrication method

    CN102290595A

  • Lithium ion battery, manufacturing method of lithium ion battery and electronic device

    CN107681192A

  • Photo-assisted enhanced secondary battery and preparation method thereof

    CN112310468A

  • Photoelectric energy storage device and preparation method thereof

    CN113838981A

  • Photovoltaic and solid-state battery photoelectric integrated energy storage system and preparation method

    CN118646364A